Diagnostic competence of teachers in the context of psycho-pedagogical assistance at school - Lilianna Klimek (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Professionalism emphasizes the importance of specific and high competences. This approach also applies to modern teaching, as a professional teacher is primarily a competent one. The psycho-pedagogical literature names various competencies to be acquired and developed by teachers. The teacher's diagnostic competence also can be frequently found in the classifications of teacher's competences. In their daily didactic and pedagogic work, this competence enables teachers to timely notice any difficulties or talents children may show, as well as to identify their individual psycho-physical possibilities and recognize their education and development needs. The teacher's diagnostic competence is necessary for optimal and efficient arranging of psycho-pedagogical assistance at school. An accurate diagnosis established by the child's teachers allows them to determine more productive methods of work with the child, to help the child to reduce or eliminate his/her problems, as well as to increase his/her motivation to work. This article concerns the teacher's diagnostic competence in the context of the psycho-pedagogical assistance students receive at school.